2021
DOI: 10.1111/opo.12817
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of axial length growth in a German cohort of healthy children and adolescents

Abstract: Purpose To generate continuous growth curves for axial length (AL) in German children. We hypothesise that percentile curves of AL can be used as a predictive measure of myopia. Methods In this longitudinal and cross‐sectional LIFE Child Study, children’s non‐cycloplegic refraction data was collected using the Zeiss i.Profiler plus while AL was measured using the Haag‐Streit Lenstar. Reference growth curves were estimated as a continuous non‐parametric function of age. Results Data from 4511 visits of 1965 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 24 publications
5
51
1
8
Order By: Relevance
“…In addition, the authors have concluded that the percentile curves of axial length can be used as a predictive measure for the likelihood of developing as well as the progression of myopia. 22 In agreement with the previous reports, the axial length was one of the biometric variables in our generated model in the present study. Sanz Diez et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the authors have concluded that the percentile curves of axial length can be used as a predictive measure for the likelihood of developing as well as the progression of myopia. 22 In agreement with the previous reports, the axial length was one of the biometric variables in our generated model in the present study. Sanz Diez et al .…”
Section: Discussionsupporting
confidence: 93%
“…20 Similarly, Sanz Diez et al 21 have reported a clinical model for the prediction of myopia development based on the creation of percentile curves of axial length in school-aged children from Wuhan in central China (N=12,554). Very recently, Truckenbrod et al 22 have reported correlation curves for axial length by spherical equivalent, age, or gender in German children between 2-18 years of age (N=1965). In addition, the authors have concluded that the percentile curves of axial length can be used as a predictive measure for the likelihood of developing as well as the progression of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…3 zeigt eine aus den epidemiologischen Wachstumsdaten von Truckenbrod etal. [28] ermittelteund miteigenen epidemiologischen Erhebungen an deutschen Schulkindern [16,17]…”
Section: Bisherige Studienergebnisseunclassified
“…Zusätzlich zur Refraktion ist bei der Therapiekontrolle auch die regelmäßige und exakte Messung der Achslänge unerlässlich. Durch das Eintragen dieser Werte in die Perzentilenkurven von Tideman et al [27] oder Truckenbrod et al [28] kann der Verlauf des individuellen Myopierisikos und damit die Wirksamkeit der Myopietherapie beurteilt werden.…”
Section: Therapiekontrolle Und Zusätzliche Therapieoptionenunclassified
“…Es findet sich der aus der Literatur bekannte Unterschied, dass in derselben Altersklasse Augen von Jungen signifikant länger sind als die von Mädchen [21,22].…”
Section: Umfangreiche Erhebung Der Biometrieunclassified